Ciencia e investigación agraria 2017
DOI: 10.7764/rcia.v44i3.1721
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of fungicide-resistant Botrytis cinerea populations isolated from ‘Thompson Seedless’ table grapes in the Central Valley of Chile

Abstract: were sensitive to all fungicides tested; from north to south, the frequency of sensitive isolates in the regions of Valparaiso, Metropolitana and O'Higgins ranged from 48.15% to 21.1% and 5.88%, respectively. Four hundred and twenty isolates (79%) showed resistance to single or multiple fungicides, 134 (25.4%) were simultaneously resistant to azoxystrobin and pyrimethanil. No fludioxonil-resistant isolates were found, indicating that fludioxonil has great potential for gray mold control in table grapes in Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The limitation in the number of fungicide sprays per season can, in fact, slow down the selection of resistant strains . The percentage of strains resistant to boscalid (2‐6%) is in line with that reported in other studies and lower than that reported for German vineyards, where the frequency of boscalid‐resistant strains reached up to 70% . Resistance to SDHI is of relatively recent discovery, and could probably be related to the increased use of the class .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The limitation in the number of fungicide sprays per season can, in fact, slow down the selection of resistant strains . The percentage of strains resistant to boscalid (2‐6%) is in line with that reported in other studies and lower than that reported for German vineyards, where the frequency of boscalid‐resistant strains reached up to 70% . Resistance to SDHI is of relatively recent discovery, and could probably be related to the increased use of the class .…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, particular attention should be taken in monitoring its evolution in the field. Resistance to APs has been frequently reported in grapevine fields, where the percentage of resistant isolates can be lower than 10%, as found in the present study, or reach values ranging from 30 to 80% . Resistance to APs was detected early in the 2000s and is particularly widespread, however it proved to be unstable in absence of selection pressure: this could help to explain the wide variability in the diffusion of resistant strains found in the literature.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Currently, the management of the disease is affected by the selection of B. cinerea isolates resistant to fungicides [ 3 ]. In a study realized in table grapes of Thompson Seedless variety in the Central Valley of Chile, it was demonstrated that only 1% of the B. cinerea isolates was sensitive to all of fungicide families [ 4 ]. Therefore, new alternatives for the control of this disease are necessary.…”
Section: Introductionmentioning
confidence: 99%